La competitividad de la fresa de Zamora, Michoacán en el mercado externo de Estados Unidos, 1990-2006 - González Sosa, Judit (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
The present work is guided to know which was the level of competitiveness of the Zamora, Michoacán, strawberry, in the market of The United States, during the period of 1990-2006. For which, it were use the indexes of revealed comparative advantage published by Balassa and Vollrath and the systemic competitiveness model proposed by René Villarreal, sustained in six levels: Microeconomic, Mesoeconómic, Macroeconomic, International, Institutional and Political-social, as link between both, we find that, the indexes of revealed comparative advantage form a part of the indicators used to measure the level macro of the systemic competitiveness. When we obtain the indexes of revealed competitiveness, it appears that, in the first years after the entry into force of the Agreement of Free Trade with The United States and Canada, Mexico had the competitive advantage of the strawberry opposite to The United States, but from the year 2000 until 2006, The United States presents a revealed top competitiveness compared with Mexico. For the results of the fieldwork, it was known that the principal limitations that have the producers of Zamora strawberry to raise his competitiveness are the access limited to the credit, problems of commercialization and high costs of production as consequence of a rise of price in the raw material.

El presente trabajo está encaminado a conocer cuál fue el nivel de competitividad de la fresa de Zamora, Michoacán, en el mercado de Estados Unidos, durante el periodo de 1990-2006. Para lo cual, se utilizaron los Índices de ventaja comparativa revelada publicados por Balassa y Vollrath y el modelo de competitividad sistémica propuesto por René Villarreal, sustentado en seis niveles: Microeconómico, Meso económico, Macroeconómico, Internacional, Institucional y Político-Social, como vínculo entre ambos, encontramos que, los Índices de ventaja comparativa revelada forman parte de los indicadores utilizados para medir el nivel macro de la competitividad sistémica. Al obtener los Índices de ventaja comparativa revelada, se observa que, en los primeros años después de la entrada en vigor del Tratado de Libre Comercio con Estados Unidos y Canadá, México poseía la ventaja competitiva de la fresa frente a Estados Unidos, pero a partir del año 2000 y hasta el 2006 es Estados Unidos el que presenta una competitividad revelada mayor con relación a México. En cuanto a los resultados del trabajo de campo, se conoció que las principales limitantes que tienen los productores de fresa de Zamora para elevar su competitividad son el acceso limitado al crédito, problemas de comercialización y altos costos de producción derivados de una alza de precio en los insumos.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2010-0013; Comercio internacional; Competitividad; Mercado externo; VCR; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/947